Oxygen uptake kinetics in all-out arm stroke, leg kicking and whole stroke front crawl 100-m swims - Rodriguez, F. A.; Lätt, E.; Jürimäe, J.; Mäestu, J.; Purge, P.; Rämson, R.; Haljaste, K.; Keskinen, K. L.; Jürimäe, T. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Arms and legs are often trained separately to obtain specific muscle adaptations along with whole body training. However, studies of VO2 kinetics have been conducted only in whole stroke (Rodriguez et al., 2003). This study examined VO2 on-kinetics during all-out 100-m front crawl arm stroke, leg kicking and whole body swimming. METHODS: 36 swimmers (26 M, 10 F) performed three all-out 100-m swims in random order (A: arms stroke, L: leg kicking, S: whole stroke). Breath-by-breath VO2 values were measured using a swimming mask attached to a portable gas analyzer (MetaMax 3B, Cortex). Phase I (cardiodynamic component) was computed as a time delay (TD) for Phase II (primary component) and the latter was then described using single [VO2 (t) = A0+A1(1.e.(t-TD)/ )] and double exponential models. VO2 parameters were compared using paired (A/L/S) and unpaired (M/F) t-tests (p. =0.05). RESULTS: There were no differences between single and double exponential curve fitting convergence parameters. Mean SD values for main parameters during A, L, and S, respectively, were as follows. TD (Phase I): 13.7+/-4.2, 14.0+/-4.2, 13.8+/-4.7 s (M), and 15.9+/-5.1, 19.5+/-5.3, 15.1+/-4.9 s (F). Total amplitude: 2.506+/-0.613, 2.681V0.538, 3.084+/-0.712 mL/min (M), and 1.817+/-0.229, 2.161+/-0.161, 2.431+/-0.2512 mL/min (F). Time constant ( ): 12.6+/-4.4, 9.9+/-2.8, 9.0+/-2.9 s (M), and 11.9+/-5.4, 10.6+/-4.1, 9.7+/-4.0 s (F). DISCUSSION: In either sex, VO2 kinetics attained higher amplitudes at S, followed by L and A. M reached higher amplitudes in all swims as compared with F. Time constants for S were lower than in a previous report (Rodriguez et al. 2003), although in that study the cardiodynamic component was not isolated. During A and L, 81 and 87% (M) and 75 and 89% of VO2 (F) of respective S amplitude was attained, similar to previously reported values during a 6-min flume swim (Ogita et al. 1996), thus confirming that the aerobic energy release in the active muscle groups involved in A plus L cannot be fully reached during S because of cardiorespiratory limitations.